2020
DOI: 10.31011/reaid-2020-v.93-n.0-art.808
|View full text |Cite
|
Sign up to set email alerts
|

Medidas de prevenção da COVID-19 em pessoas que vivem com diabetes mellitus

Abstract: Objetivo: Investigar as evidências científicas sobre as medidas de prevenção da Covid-19 em pessoas que vivem com diabetes mellitus. Método: Revisão integrativa da literatura, realizada no período de 20 de junho a 20 de julho de 2020, baseada na seguinte questão norteadora: quais medidas de prevenção da Covid-19 em pessoas que vivem com diabetes? Foram utilizadas as bases de dados: Medline/Pubmed, LILACS e CINAHL, cruzando-se os descritores: “diabetes mellitus” AND “coronavirus infections” e “diabetes mellitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(58 reference statements)
0
2
0
2
Order By: Relevance
“…Se recomienda el uso de mascarilla como medida importante en la prevención del COVID-19, pues protege las vías respiratorias del contacto con el virus, siendo medida de bajo costo para población en general (12,14,15,23) . Sin embargo, esta medida no es suficiente para brindar nivel adecuado de protección, y se deben adoptar otras medidas no farmacológicas, como higiene de las manos (12,14,15,23) con el uso de agua y jabón para eliminar la suciedad o el uso del alcohol al 70%, cuando no sea posible utilizar agua y jabón (29) .…”
Section: Discussionunclassified
“…Se recomienda el uso de mascarilla como medida importante en la prevención del COVID-19, pues protege las vías respiratorias del contacto con el virus, siendo medida de bajo costo para población en general (12,14,15,23) . Sin embargo, esta medida no es suficiente para brindar nivel adecuado de protección, y se deben adoptar otras medidas no farmacológicas, como higiene de las manos (12,14,15,23) con el uso de agua y jabón para eliminar la suciedad o el uso del alcohol al 70%, cuando no sea posible utilizar agua y jabón (29) .…”
Section: Discussionunclassified
“…A study showed the importance of the practice of prevention care to reduce the spread of the virus, among them, social isolation, hand hygiene and the use of a face mask (15) . In relation to specific prevention measures, scientific evidence shows that to prevent, people with diabetes mellitus need to pay attention to the proper intake of liquids, improve food consumption, especially complex carbohydrates, maintain treatment with oral hypoglycemic agents and insulin therapy, monitor blood glucose levels, perform physical exercise, under the supervision of physical education professionals; cease the use of tobacco, seek vaccination against respiratory diseases, and seek medical attention by telemedicine (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it will be possible to promote the adequacy and effectiveness of prevention measures, by means of self-care, given that individuals who live with the disease need to be part of or take a leading role in the decisionmaking process related to their own health. It is important to highlight that, as there was no accurate form for measuring the abovementioned activities, a review was conducted in the literature in order to identify the measures to prevent covid-19 in people living with diabetes (12) . This review supported the construction of a form containing twenty questions in general prevention measures and six issues in specific prevention measures, according to the above subcategories.…”
Section: Introductionmentioning
confidence: 99%
“…Entre estas, o Diabetes Mellitus (DM), distúrbio endócrino caracterizado por falhas no metabolismo da glicose, vem sendo associado a elevados índices de mortalidade entre pacientes acometidos pela COVID-19, devido a sua maior capacidade de inflamação metabólica e a liberação de uma diversidade de citocinas aos quais os mesmos encontram-se continuamente predispostos (Silva et al, 2020).…”
Section: Introductionunclassified